2005
DOI: 10.1128/jvi.79.9.5548-5556.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptional Transactivation Function of HBx Protein Is Important for Its Augmentation Role in Hepatitis B Virus Replication

Abstract: The role and functional domain of hepatitis B virus (HBV) X protein (HBx) in regulating HBV transcription and replication were investigated with a transient transfection system in the human hepatoma cell line HepG2 using wild-type or HBx-minus HBV genome constructs and a series of deletion or mutation HBx expression plasmids. We show here that HBx has augmentation effects on HBV transcription and replication as a HBV mutant genome with defective X gene led to decreased levels of 3.5-kb HBV RNA and HBV replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
195
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(215 citation statements)
references
References 46 publications
20
195
0
Order By: Relevance
“…In transgenic mice, HBx is not essential for HBV replication, but it can enhance viral replication (Reifenberg et al, 2002;Xu et al, 2002). Recently, in vitro experiments suggest that HBx stimulates HBV replication via its transactivation function (Melegari et al, 2005;Tang et al, 2005). It has been demonstrated that HBx action on viral replication may be dependent to modulation of calcium homeostasis, which provides novel clues for HBx biology (Bouchard et al, 2001(Bouchard et al, , 2003Choi et al, 2005).…”
Section: Hbxmentioning
confidence: 99%
“…In transgenic mice, HBx is not essential for HBV replication, but it can enhance viral replication (Reifenberg et al, 2002;Xu et al, 2002). Recently, in vitro experiments suggest that HBx stimulates HBV replication via its transactivation function (Melegari et al, 2005;Tang et al, 2005). It has been demonstrated that HBx action on viral replication may be dependent to modulation of calcium homeostasis, which provides novel clues for HBx biology (Bouchard et al, 2001(Bouchard et al, , 2003Choi et al, 2005).…”
Section: Hbxmentioning
confidence: 99%
“…25,31,32 Replication of the HBx-deficient HBV replicon in HepG2 cells was reduced by threefold compared with wild-type HBV, suggesting that HBx plays a stimulatory role in HBV replication. 33 The information on HBx protein continues to grow, although many of the roles and functions of HBx remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Although initial studies suggested that HBx was not required for virus replication in cell culture (18), experiments with the highly related woodchuck hepatitis virus (WHV) system indicate that the WHV X protein (WHx) is required for virus replication in vivo (19)(20)(21)(22). Studies performed using a plasmid-based replication assays that use greater-than-unit-length HBV genomes transfected in HCC cell lines or injected via the mouse tail vein under hydrodynamic conditions have repeatedly confirmed that HBx potentiate HBV replication (23)(24)(25)(26)(27).…”
Section: H Epatitis B Virus (Hbv) Infection Is a Major Health Problemmentioning
confidence: 99%